The development of mental processes in preschool children - Tolipova Ozoda Ikromovna (Research Parks Publishing LLC, 2021)
The article discusses issues such as the upbringing of kindergarten-age children, their mastery of complex movements, the formation of basic hygiene, cultural and labor skills, speech development, and the formation of the first buds of social morality and aesthetic taste.